OUTCOMES FOR PRETERM BABIES DURING THE NEONATAL PERIOD IN KISII TEACHING AND REFERRAL HOSPITAL, KENYA - Mochama, Rhodah S.; Esamai, Fabian; Rotich, Evelyne (Global Journal of Health Sciences, 2019)
Purpose: Preterm birth is a global problem with the greatest burden experienced in sub-Saharan Africa and South Asia. In Kenya it is estimated that 12.3/100 live births are born preterm and prematurity is the leading cause of death in the first month of life, contributing to 35% of all neonatal mortality. In high income countries survival rate for preterm babies has increased due to offering care that is evidence based. However, in middle and low income countries the uptake of desired practices is low leading to poor outcomes. The aim of the study was to describe the outcomes for preterm babies during the neonatal period in Kisii Teaching and Referral Hospital (KTRH). Methods: A cross sectional descriptive study was conducted in the newborn unit of KTRH between April and May 2015. Fifty three preterm babies' parents consented to participate in the study through census sampling method. Data was collected using a checklist and analyzed using descriptive statistics. Results: Thirty three (62%) preterm babies were born in the facility and 20(38%) were referred from other facilities. The outcomes experienced included respiratory distress syndrome 30(56.6%), feeding difficulties 28(52.8%), jaundice 12(22.6%), Hypothermia 1(1.9%), anemia 5(9.8%), hypoglycemia 1(1.9%), sepsis 4(7.5%), hemolytic disease of the newborn 1(1.9), necrotizing enterocolitis 1(1.9%) and death 26(49.1) where 19(73.1%) had RDS, and 17(65.4%) had difficulty in feeding. Conclusion: Respiratory distress syndrome and difficulty in feeding were the most common complications experienced by the preterm baby. Recommendations: This study recommends prompt and adequate management of preterm babies diagnosed with RDS and feeding problems